Update on minimally invasive surgery and benign prostatic hyperplasia - Amanda S.J. Chung; Henry H. Woo (Asian Journal of Urology)
Transurethral resection of the prostate (TURP) became the gold standard surgical treatment for benign prostatic obstruction without undergoing randomized controlled trials against the predecessor standard in open suprapubic prostatectomy. TURP has historically been associated with significant morbidity and this has fuelled the development of minimally invasive surgical treatment options. Improvements in perioperative morbidity for TURP has been creating an ever increasing standard that must be met by any new technologies that are to be compared to this gold standard. Over recent years, there has been the emergence of novel minimally invasive treatments such as the prostatic urethral lift (PUL; UroLift System), convective WAter Vapor Energy (WAVE; Rezum System), Aquablation (AQUABEAM System), Histotripsy (Vortx Rx System) and temporary implantable nitinol device (TIND). Intraprostatic injections (NX-1207, PRX-302, botulinum toxin A, ethanol) have mostly been used with limited efficacy, but may be suitable for selected patients. This review evaluates these novel minimally invasive surgical options with special reference to the literature published in the past 5 years.